Whole genome sequencing of silver carp (Hypophthalmichthys molitrix) and bighead carp (Hypophthalmichthys nobilis) provide novel insights into their evolution and speciation. (26th December 2020) - Jian, Jianbo; Yang, Liandong; Gan, Xiaoni; Wu, Bin; Gao, Li; Zeng, Honghui; Wang, Xuzhen; Liang, Zhiqiang; Wang, Ying; Fang, Lihua; Li, Jie; Jiang, Sanjie; et al.
Abstract: The edible silver carp ( Hypophthalmichthys molitrix ) and bighead carp ( H. nobilis ), which are two of the "Four Domesticated Fish" of China, are cultivated intensively worldwide. Here, we constructed 837‐ and 845‐Mb draft genome assemblies for the silver carp and the bighead carp, respectively, including 24, 571 and 24, 229 annotated protein‐coding genes. Genetic maps, anchoring 71.7% and 83.8% of all scaffolds, were obtained for the silver and bighead carp, respectively. Phylogenetic analysis showed that the bighead carp formed a clade with the silver carp, with an estimated divergence time of 3.6 million years ago; the time of divergence between the silver carp and zebrafish was 50.7 million years ago. An East Asian cyprinid genome‐specific chromosome fusion took place ~9.2 million years after this clade diverged from the clade containing the common carp and Sinocyclocheilus . KEGG and GO analyses indicated that the expanded gene families in the silver and bighead carp were associated with diseases, the immune system and environmental adaptations. Genomic regions differentiating the silver and bighead carp populations were detected based on the whole‐genome sequences of 42 individuals. Genes associated with the divergent regions were associated with reproductive system development and the development of primary female sexual characteristics. Thus, our results provided a novel systematic genomic analysis of the East Asian cyprinids, as well as the evolution and speciation of the silver carp and bighead carp.